2013
DOI: 10.1016/j.seizure.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Five cases of new onset refractory status epilepticus (NORSE) syndrome: Outcomes with early immunotherapy

Abstract: In our experience, early immunotherapy has been associated with good outcomes in NORSE. Multicentre collaboration is required to establish the diagnostic criteria and appropriate management of patients presenting with NORSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 21 publications
4
101
0
2
Order By: Relevance
“…Early immunotherapy with intravenous methylprednisolone (IvMP), intravenous immunoglobulin (IvIg) or both, was recently reported to be efficient in three of five adults suffering from new-onset refractory SE who received these medications, whereas the two other patients of the series who did not receive immunomodulatory treatments had a more severe outcome. The results of previous case descriptions with similar approaches described in that article were less convincing, however [85]. Corticosteroids are used as first-line immunotherapy and have their place in the treatment of SE even in the absence of an autoimmune etiology, since SE may be associated with an inflammatory response and with a disruption of the BBB [105].…”
Section: Autoimmunity and Inflammation In Status Epilepticusmentioning
confidence: 88%
“…Early immunotherapy with intravenous methylprednisolone (IvMP), intravenous immunoglobulin (IvIg) or both, was recently reported to be efficient in three of five adults suffering from new-onset refractory SE who received these medications, whereas the two other patients of the series who did not receive immunomodulatory treatments had a more severe outcome. The results of previous case descriptions with similar approaches described in that article were less convincing, however [85]. Corticosteroids are used as first-line immunotherapy and have their place in the treatment of SE even in the absence of an autoimmune etiology, since SE may be associated with an inflammatory response and with a disruption of the BBB [105].…”
Section: Autoimmunity and Inflammation In Status Epilepticusmentioning
confidence: 88%
“…The studies included are highlighted in Table 1. A retrospective analysis of five patients with NORSE by Gall et al showed that three out of five patients who received immunotherapy (steroids, IVIg, and/or azathioprine) had seizures subsequently controlled on AEDs, with only one patient developing mild cognitive decline [9]. The fourth patient died (no IT administered), and the fifth patient's outcome was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This has prompted the eponym NORSE, for New Onset Refractory Status Epilepticus (Wilder-Smith et al, 2005). We found four published series of NORSE in adults (Costello et al, 2009;Gall et al, 2013;Van Lierde et al, 2003;Wilder-Smith et al, 2005) (Table 2). Altogether, they included 24 young, previously healthy patients with RSE lasting Two remained impaired and dependent Two remained impaired but were independent One had a "good outcome" Three survivors had refractory epilepsy; one was seizure-free on 2 ASDs; one was seizurefree without any ASD (Continued) from 6 to 191 days.…”
Section: Cryptogenic Refractory Status Epilepticus or New Onset Refrmentioning
confidence: 90%